Prevention of neointimal hyperplasia after coronary artery bypass graft via local delivery of sirolimus and rosuvastatin: network pharmacology and in vivo validation - Ji-yeon Ryu; Eui Hwa Jang; JiYong Lee; Jung-Hwan Kim; Young-Nam Youn (Journal of Translational Medicine, 2024)
Abstract Background Coronary artery bypass graft (CABG) is generally used to treat complex coronary artery disease. Treatment success is affected by neointimal hyperplasia (NIH) of graft and anastomotic sites. Although sirolimus and rosuvastatin individually inhibit NIH progression, the efficacy of combination treatment remains unknown. Methods We identified cross-targets associated with CABG, sirolimus, and rosuvastatin by using databases including DisGeNET and GeneCards. GO and KEGG pathway enrichment analyses were conducted using R studio, and target proteins were mapped in PPI networks using Metascape and Cytoscape. For in vivo validation, we established a balloon-injured rabbit model by inducing NIH and applied a localized perivascular drug delivery device containing sirolimus and rosuvastatin. The outcomes were evaluated at 1, 2, and 4 weeks post-surgery. Results We identified 115 shared targets between sirolimus and CABG among databases, 23 between rosuvastatin and CABG, and 96 among all three. TNF, AKT1, and MMP9 were identified as shared targets. Network pharmacology predicted the stages of NIH progression and the corresponding signaling pathways linked to sirolimus (acute stage, IL6/STAT3 signaling) and rosuvastatin (chronic stage, Akt/MMP9 signaling). In vivo experiments demonstrated that the combination of sirolimus and rosuvastatin significantly suppressed NIH progression. This combination treatment also markedly decreased the expression of inflammation and Akt signaling pathway-related proteins, which was consistent with the predictions from network pharmacology analysis. Conclusions Sirolimus and rosuvastatin inhibited pro-inflammatory cytokine production during the acute stage and regulated Akt/mTOR/NF-κB/STAT3 signaling in the chronic stage of NIH progression. These potential synergistic mechanisms may optimize treatment strategies to improve long-term patency after CABG. Graphical Abstract